2022
DOI: 10.1021/acsomega.2c00283
|View full text |Cite
|
Sign up to set email alerts
|

Design of Zr- and Al-Doped *BEA-Type Zeolite to Boost LDPE Cracking

Abstract: Nowadays, the increase in plastic waste is causing serious environmental problems. Catalytic cracking has been considered a promising candidate to solve these problems. Catalytic cracking has emerged as an attractive process that can produce valuable products from plastic wastes. Solid acid catalysts such as zeolites decompose the plastic waste at a lower temperature. The lower decomposition temperature may be desirable for practical use. Herein, we synthesized both Zr- and Al-incorporated Beta zeolite using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
(108 reference statements)
0
9
0
Order By: Relevance
“…Kokuryo and co-workers revealed that the synthesized Zr-beta showed activity on LDPE cracking superior to that of a conventional beta zeolite due to the enhanced Lewis acidity derived from the Zr species. 146 Likewise, Pyo et al found that Ga-ZSM-5 revealed the lowest apparent activation energy (E a ) at 110 kJ/mol, compared with HUSY and other HZSM-5 catalysts (122−172 kJ/mol), which explained its high activity on PP cracking. 150 More detailed research on the catalytic cracking of light hydrocarbons over metal-doped zeolite could provide more insight.…”
Section: Metal/zeolite Composite Catalyst In Catalytic Cracking Of Po...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kokuryo and co-workers revealed that the synthesized Zr-beta showed activity on LDPE cracking superior to that of a conventional beta zeolite due to the enhanced Lewis acidity derived from the Zr species. 146 Likewise, Pyo et al found that Ga-ZSM-5 revealed the lowest apparent activation energy (E a ) at 110 kJ/mol, compared with HUSY and other HZSM-5 catalysts (122−172 kJ/mol), which explained its high activity on PP cracking. 150 More detailed research on the catalytic cracking of light hydrocarbons over metal-doped zeolite could provide more insight.…”
Section: Metal/zeolite Composite Catalyst In Catalytic Cracking Of Po...mentioning
confidence: 99%
“…First, zeolites doped with metal atoms (i.e., Zn, Zr, Ga, etc.) could improve the conversion rate and selectivity of the catalytic cracking reaction by tuning the acidity of the pristine zeolite catalysts. , More importantly, the composite catalysts could catalyze polyolefin hydrocracking (including hydrogenolysis) due to the high activity for H 2 activation on the supported active metal clusters and nanoparticles. ,,,,, In addition, their catalytic activities and selectivities could be further adjusted by a metal/acid synergy effect.…”
Section: Metal/zeolite Composites In Catalytic Conversion Of Polyolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Previously, the Lewis acidity of beta zeolites was demonstrated to be enhanced by introducing various metals, which successfully lowered the degradation temperature of polyolefins. [35,36] Although zeolites are excellent solid acid catalysts, deactivation occurs owing to coke deposition. [37] Coke is formed by the polycyclization of aromatics formed during the reaction [38] and covers the active sites or blocks the pores, thereby reducing the catalytic performance of the zeolite.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, *BEA‐type zeolites, known as beta zeolites, have been investigated as a polymer cracking catalyst [34] . Previously, the Lewis acidity of beta zeolites was demonstrated to be enhanced by introducing various metals, which successfully lowered the degradation temperature of polyolefins [35,36] …”
Section: Introductionmentioning
confidence: 99%